Reliability and validity of the Brazilian version of the Pittsburgh Sleep Quality Index in adolescents - Muana H.P. Passos; Hítalo A. Silva; Ana C.R. Pitangui; Valéria M.A. Oliveira; Alaine S. Lima; Rodrigo C. Araújo (Brazilian Society of Pediatrics, 2017)
Objective: To evaluate the reliability and validity of the Brazilian version of the Pittsburgh Sleep Quality Index. Methods: 309 adolescents, subdivided into a sample of 209 subjects, of whom 25 were reassessed, and another sample of 100 adolescents. Reliability was assessed using Cronbach's α‐values, intraclass correlation coefficient, Standard Error of Measure, Minimum Detectable Change, and Bland-Altman plotting. Exploratory analysis of the questionnaire components was performed based on the sample of 209 adolescents. Confirmatory factor analysis was performed with a sample of 100 individuals. Results: The sample of 209 participants had a mean age of 14.38 (±1.94) years, comprising 80 (38.3%) girls and 129 (61.7%) boys. The sample of 100 adolescents had a mean age of 13.66 (±2.35) years, comprising 51 (51%) girls and 49 (49%) boys. The questionnaire obtained a Standard Error of Measure = 1.12 and Minimum Detectable Change = 3.10. Cronbach's α was 0.71 and the Intraclass Correlation Coefficient was 0.65 (95% CI: 0.21-0.85). The factor analysis showed that the best model of components was the one that consisted of two factors, excluding the component on the use of sleep medications. Conclusion: The questionnaire showed high internal consistency and moderate reliability. Furthermore, a model with two factors seems to be the most appropriate to evaluate the quality of sleep in adolescents.